Differentiated use and value of river and riparian ecosystem services and local perspectives on future safeguarding: A case study of the upper Mutale sub-catchment, Limpopo River Basin, South Africa - Ragimana, Phumudzo (Department of Environmental and Geographical Science, 2026)
Over the past five decades, human-driven changes in natural ecosystems have resulted in biodiversity loss and a decline in ecosystem services, particularly affecting freshwater ecosystems. The response to these challenges has led to the adoption of nature-based solutions, emphasizing the restoration and sustainable management of ecosystems to enhance biodiversity and human well-being. Advocates stress the necessity of local engagement and knowledge integration in nature-based solutions, underscoring the potential adverse effects on vulnerable social groups if these interactions are neglected. This study focused on Tshiombo Village near the Mutale River in South Africa, aiming to contribute to knowledge regarding restoration and sustainable management of river and riparian ecosystem services. Using an explanatory sequential mixed-methods design, the research assessed the differentiated use and value of these services among social groups, perceived changes in service availability, potential drivers of changes, and the consideration of nature-based solutions. Survey results revealed a high reliance on the Mutale River and its surroundings for various provisioning, cultural, and regulating ecosystem services. Freshwater for non-drinking domestic use and crop irrigation, delivered through a concrete canal, emerged as the most vital ecosystem service supporting community livelihoods. Women emerged as primary users, emphasizing the importance of the river for irrigation and non-drinking domestic use. Perceived declines in ecosystem services over the past decade were linked to local use and consumption and land use and cover change. While respondents showed limited awareness of nature-based actions, they expressed high awareness and preference for grey infrastructure options. Interviews with key informants aligned with survey results, highlighting a strong preference for grey infrastructure solutions, especially a concrete canal, to address declines in ecosystem services, particularly in relation to water scarcity issues. Here, a range of different social groups and resource users—despite acknowledging environmental decline—seemed only aware of grey infrastructure rather than nature-based solutions, despite being presented with some nature-based options. In contrast, local teachers were one core group that advocated for a focus on restoring and sustainably managing the environment. They also emphasized the importance of environmental literacy and inter-generational learning to increase the awareness of community members of nature-based solutions to addressing declines in ecosystem services such as water supply. This study emphasized the diversity of how different social groups use and value ecosystem services, underscoring their collective importance in the community. Most community members linked the use of grey infrastructure to improving losses of ecosystem services such as water supply. This showed their awareness and preference leaned towards grey infrastructure over nature-based solutions. The study underscores the necessity for hybrid approaches, combining grey and natural infrastructure, to ensure the sustainable delivery of ecosystem services in this rural community, which is more commonly found in urban literature on nature-based approaches. Further, environmental literacy is important to pair the community's grey infrastructure preferences for increased water accessibility with nature-based solutions to prevent future grey infrastructure damage and maintenance requirements, e.g., conservation agriculture could reduce the sedimentation of the concrete canal. This study highlights the need for hybrid solutions, combining grey and nature-based approaches, and underscores the importance of community involvement and human-centered approaches for effective ecosystem restoration and management, particularly in rural areas. The findings provide valuable insights for developing strategies that address the challenges faced by the Tshiombo Village community in safeguarding ecosystem services and enhancing well-being.